Structure of the southwest monsoon near the equator during Monex 1973 - PANT, M. C. (MAUSAM, 1976)
The structure, of, the southwest monsoon near the equator over the west Indian Ocean during June 1973 has been studied by utilising MONEX 1973 data. It is found that the equatorial belt extending from the east African coast to about 75°E can broadly be divided into three regions, viz., (i) the western region-extending from the east African coast to, about 56°E (ii) the central region -from 56° to about 65°E and (iii) the eastern region-east of 650 E. The vertical fields of wind, temperature and moisture markedly differ from each other over these region . While over the western, and eastern regions deep convective activity is observed, the central region is characterized by a large-scale sinking of air in the mid-tropospheric levels. Due to this dynamic process, the mid-tropospheric westerlies suffer considerable modification and become increasingly warm and dry downstream over the central region.